Qualitative Study on the Implementation of the Partnership Model Without Capital in the Development of AA Cilok Business - Rahma Ramadhani; Veta Lidya Delimah Pasaribu (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the implementation of a zero-capital partnership model in the development of micro-enterprises, with a case study of Cilok AA in Bekasi. The model relies on trust as the foundation of cooperation without requiring initial investment. Using a qualitative approach and case study method, data were collected from the experiences of business owners and partners. The results show that this model supports partners without the burden of initial capital, but faces challenges such as low partner commitment, inconsistent service understanding, and limited performance monitoring. In conclusion, the model positively impacts business growth, but requires regular evaluation, consistent control, and equal training for sustainability.